1993
DOI: 10.1210/en.132.6.2709
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated regulation of rat ovarian function: interleukin-1 stimulates the accumulation of a 92-kilodalton gelatinase

Abstract: It is known that the mammalian ovary possesses a complete interleukin-1 (IL-1) system replete with ligands, receptors, and a receptor antagonist. To further assess the hypothesis that IL-1 may play an intermediary role in gonadotropin-triggered ovulation, we have set out to determine whether IL-1 is capable of promoting ovarian collagenase biosynthesis, an established component of the ovulatory cascade. Untreated cultured whole ovarian dispersates from immature (25 day old) rats constitutively elaborated sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…IL-1 also increased the productions of prostaglandins [11], hyaluronic acid and proteoglycan [14] and gelatinase [15], which may be related to changes associated with the ovulatory process. In fact, IL-1f3 stimulated ovulation in rabbits [23], and an anti-ovulatory effect of IL-1 receptor antagonist was demonstrated in rats [24,25], but the effect of IL-1 on ovarian functions is dependent on the stage of follicular development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1 also increased the productions of prostaglandins [11], hyaluronic acid and proteoglycan [14] and gelatinase [15], which may be related to changes associated with the ovulatory process. In fact, IL-1f3 stimulated ovulation in rabbits [23], and an anti-ovulatory effect of IL-1 receptor antagonist was demonstrated in rats [24,25], but the effect of IL-1 on ovarian functions is dependent on the stage of follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage in particular is one of the key factors in the immune system and has been reported to be present in the ovary [3,4] [15]. It is also reported that IL-1 activity in human macrophages is influenced by gonadal steroids [16].…”
mentioning
confidence: 99%
“…Third, some components of the intraovarian IL-1 system (e.g., IL-1 ␤ and the type I IL-1 receptor) appear to be expressed in vivo, mainly during a narrow periovulatory window (6)(7)(8)(9)(10)(11)(12). Fourth, IL-1 ␤ has been shown to induce a host of ovulation-associated phenomena in vitro, such as the promotion of prostaglandin production (13)(14)(15)(16), the stimulation of hyaluronic acid biosynthesis (17), the induction of collagenase activity (18), and the activation of nitric oxide synthase activity (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The 92-kDa type IV matrix metalloproteinase (92-kDa gelatinase B also known as MMP-9) plays a major role in cell migration in both physiological and pathological processes (1)(2)(3) by facilitating the destruction of the type IV collagencontaining basement membrane which separates the epithelial and stromal compartments (4). The 92-kDa type IV collagenase is secreted as a proenzyme (5) and subsequently activated by multiple enzymes, including cathepsin G, trypsin, stromelysin 1 (6), and 72-kDa gelatinase A (7) by the removal of 73 amino acids from the amino terminus of the protease.…”
mentioning
confidence: 99%